2015
DOI: 10.1080/01426397.2015.1029445
|View full text |Cite
|
Sign up to set email alerts
|

Are Perceived Sensory Dimensions a Reliable Tool for Urban Green Space Assessment and Planning?

Abstract: Environmental psychologists have developed varying methods for landscape assessment according to how it is perceived and experienced. In the Nordic countries, eight perceived sensory dimensions are increasingly being used as a methodological framework for expert assessments. These are serene, nature, rich in species, space, prospect, refuge, social and culture. Using an onsite questionnaire distributed to green space visitors in Helsingborg, Sweden, this study is the first to examine the representation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 44 publications
5
36
0
1
Order By: Relevance
“…In a more similar attempt, through expert objective measurement approach, it showed that PSDs can positively be associated with users judgement of restorativeness value of urban open green spaces (Peschardt and Stigsdotter 2013). However, in this study, this relationship is established through subjective experience of PSDs and potential restorativeness characteristics, rather than experts objective evaluation approach, which may cause different views in evaluation of qualities in landscape perception (Qiu and Nielsen 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a more similar attempt, through expert objective measurement approach, it showed that PSDs can positively be associated with users judgement of restorativeness value of urban open green spaces (Peschardt and Stigsdotter 2013). However, in this study, this relationship is established through subjective experience of PSDs and potential restorativeness characteristics, rather than experts objective evaluation approach, which may cause different views in evaluation of qualities in landscape perception (Qiu and Nielsen 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The relevant studies have supported the validity of assessment of green spaces with these eight perceived sensory dimensions (Qiu and Nielsen 2015;Stigsdotter et al 2017), across different cultural background (Memari et al 2017;Skärbäck et al 2015) and in context of university campus (Skarback and Grahn 2016). In this study each of eight PSD variables is measured through 3 items, which are addressed in the PSDs' studies (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The sensory perception of nature characteristics, especially, PSDs cannot be measured with landscape objective assessment approaches (De Jong et al, 2011). There are studies assessed the experienced green space characteristics, subjectively using selfreported measurement approach by lay-public participants (Lottrup et al, 2012;Stigsdotter and Grahn, 2011;Qiu and Nielsen, 2015;Memari et al, 2017). Studies supported the reliability of PSDs in measuring of green space characteristics using lay-public experiences, with similar outcomes, in different countries despite differences in culture and history (Memari et al, 2017;Sk ärb äck et al, 2015).…”
Section: 4-supportive Environment Theory (Set)mentioning
confidence: 97%
“…For instance, Peschardt and Stigsdotter (2013) asked two professional landscape architects to objectively evaluate the PSDs of nine small public urban green spaces (SPUGS) on-site. Qiu and Nielsen (2015) explained that experts assessment approach hold a dubious source to involve users' expression, ideas and feelings. Studies have shown the different viewpoints of experts and laypersons in perceiving of the landscape characteristics (Hofmann et al, 2012;Karmanov and Hamel, 2008).…”
Section: 4-supportive Environment Theory (Set)mentioning
confidence: 99%
“…The relevant studies have supported the validity of assessment of green spaces with these eight perceived sensory dimensions (Qiu and Nielsen, 2015;Stigsdotter et al, 2017), across different cultural background (Memari et al, 2017;Ska rb äck et al, 2015) and in con-text of university campus (Skarback and Grahn, 2016). In this study, each of eight PSD variables is measured through 3 items, which are addressed in the PSDs' studies (e.g.…”
Section: Methodsmentioning
confidence: 99%